Bacillus megaterium Strain CDK25, a Novel Plant Growth Promoting Bacterium Enhances Proximate Chemical and Nutritional Composition of Capsicum annuum L - Bhatt, Kalpana; Maheshwari, Dinesh Kumar (Frontiers in Plant Science, 2020)
The present study aimed to scrutinize the effect of different cow dung bacterial treatment on the nutritional value of Capsicum annuum L. Among all treatments, seeds inoculated with Bacillus megaterium (CDK25) showed significant enhancement in various proximate constituents viz., crude fiber (3.31%), crude protein (3.84%) and ash (2.53%) as compared to control. Likewise, significant increase in different nutrients contents viz., Ca (16.26 mg/100g), Mg (17.37 mg/100g), P (11.91 mg/100g), K (0.47 mg/100g), Fe (1.37 mg/100g) and Zn (0.21 mg/100g) was recorded over the control. Principal component analysis data depicts a positive correlation between different treatments with variables, validating enhancement in nutritional constituents by B. megaterium (CDK25) treatment. The study suggests the application of “B. megaterium” for achieving the persistent potential for augmenting and boosting up plant biological, functional, and nutritional assets, thereby enhancing the overall edible quality of C. annuum L. along with weathering of soil minerals.